Changes in the Presentation and Severity of Acute Appendicitis: A Comparison of the COVID-19 Pandemic and Post-Pandemic Eras - Mohammed Bu Bshait; Ahmed Kamal; Abdullah Almaqhawi; Ahmad Al Abdulqader; Haytham Alarfaj; Mohammed Albarqi; Nawaf Al Khashram; Nora AlMssallem; Fatimah Aljalal; Sara Aljaafari; Abtesam Alnaim; Sharifah Alzabdawi; et al. (Diseases)
Background: The restrictions during the COVID-19 pandemic, along with people’s avoidance of hospital exposure, led to a reduction in medical consultations and delays in care seeking. Numerous reports have shown a decrease in the number of appendectomies performed and an increased incidence of complicated appendicitis during the pandemic. We aimed to investigate these findings during and after the cessation of COVID-19-related restrictions. Methods: This retrospective cohort study was conducted in a single centre, including consecutive adult patients who underwent appendectomy for acute appendicitis during three different periods: the pandemic cohort (7 March–30 June 2020), the post-pandemic cohort (7 March–30 June 2022) and the pre-pandemic control cohort (7 March–30 June 2019). A total of 103 patients were included and divided into the three cohorts. The patients’ demographics, clinical presentation, investigations, and operative data were compared. Results: The three groups did not differ significantly regarding demographics, clinical characteristics, or the number of appendectomies. However, a duration of symptoms at presentation of less than 2 days was significantly more frequent in the pre-pandemic and post-pandemic groups than the pandemic group (p = 0.001). The interval between admission and operation was significantly shorter in the post-pandemic group than in the pandemic group. The pandemic group also showed a higher incidence of complicated appendicitis compared to the others (p = 0.025). Conclusions: The termination of the COVID-19 pandemic and its related restrictions promoted the earlier presentation of acute appendicitis cases and lowered the incidence of complicated appendicitis. This emphasises the impact of the COVID-19 pandemic on acute appendicitis.